PENGARUH PENDIDIKAN KESEHATAN PERAWATAN ORGAN REPRODUKSI DENGAN METODE JIGSAW TERHADAP PERILAKU PERSONAL HYGIENE REMAJA - I Gusti Ayu Pramitaresthi; Ida Arimurti Sanjiwani (Coping: Community of Publishing in Nursing, 2020)
Adolescence is a period of transition from childhood to adulthood, including development (physical, psychological) experienced in preparation for adulthood. One of the health problems that often arise in adolescents is due to poor personal hygiene. Health education is an effort or activity to create community behavior that is conducive to health. One of health education is reproductive health using the Jigsaw method. Jigsaw also takes the jigsaw work pattern, students carry out learning activities by working together with other students to achieve common goals. This study aims to determine the effect of health education on reproductive organ care using the Jigsaw method on adolescent personal hygiene behavior. The design of this study was a quasi experiment. The research design used was one group pre-test post-test design. Bivariate analysis was performed using non-parametric tests because the data were not normally distributed and tested by the Wilcoxon test to analyze the level of knowledge, attitudes and behavior before (pretest) and after (posttest). The results showed that there was an effect of health education on reproductive organ care using the Jigsaw method on adolescent personal hygiene behavior (p <0.05). The conclusion is that health education about the care of reproductive organs using the Jigsaw method improves the personal hygiene behavior of adolescents. Keywords: Jigsaw, Reproductive Organs Care, Personal Hygiene, Adolescents